É possível ter religião e ser laico? A escola como espaço e tempo de mediação e coexistência de discursos seculares e religiosos. - Sá, Evanilson Alves de (2024)
The research aimed to understand religion in its relationship with the public space, especially in Youth and Adult Education (EJA), in order to understand how secular and religious discourses coexist in the educational environment. In this way, the thesis was proven that it is possible to have religion and be secular and that the school is a privileged institution for mediation between secular and religious discourses. Subsequently, the experiences of this mediation in and through pedagogical practice were evaluated and the results were confirmed, and specific social practices, in interaction and dialogue with other specific social practices, resulted in the formation of subjects capable of participating in peacemaking efforts and constructive dialogues between non-believers and believers. The methodology, a qualitative paradigm, was developed through document analysis, observation and semi-structured interviews with teachers, administrators and students. The research was conducted in a school of the Municipal Education Network of Jaboatão dos Guararapes (PE/BR), located on the urban periphery, in an occupied area. Next, we present the main theoretical frameworks that support our study, our research intentions and the results that arise from them. Initially, our incursions were aimed at identifying various conceptions of secularism, linked to historical processes and their philosophical, sociological, legal and pedagogical contours, in order to approach the conceptions of collaborative secularism and Brazilian secularism. From now on, we highlight some theoretical aspects, such as the concept of habitus and the notions of state, field, capital and agent, which were converted into theoretical categories, thus, they were constructed as driving ideas to clarify our research objectives. Next, we move on to discourse theory from the perspective of Laclau and Mouffe, thus searching for a theory for data analysis. In view of this, we proceeded to reflect on the future of religion in contemporary times in a scenario of religious mutations and displacements, to better understand the meanings of the transitions between the faithful and the pilgrim, from the faithful to the half-faithful, from the religious to the spiritualized, in the context of religions remade from pre-established religions. Continuing, we sought to clarify the conceptions related to human rights, in their universalist, relativist and critical conceptions, considered as necessary to the understanding of Human Rights Education (HRE), considering its characteristics and theoretical affiliations, among them, with critical pedagogies. We also highlight EJA, its historical aspects and the context of Juvenilization of its students, to better understand the meanings and negotiations of meanings that shape secularism in pedagogical practice. Furthermore, based on empirical research and triangulation of data with the theoretical options adopted, we present the confirmation of our thesis and the possible contributions to the understanding of the relationship between State and religion and how it is projected in the educational field. Therefore, it was found that non-believers and believers of different religions and denominations coexist in the school. However, religions of African origin are invisible, their followers are secretive, discreet, very reserved, feel excluded from their religious affiliations and do not identify themselves, do not assume themselves, for fear of discrimination and prejudice. Therefore, for these subjects, the school is not secular. Therefore, we conclude that various conceptions of secularism coexist in it and that inter-religious dialogue is encouraged among religious denominations of Christian origin, which, in the context of Brazilian secularism, we qualify as incomplete or half-secularism. Finally, we conclude that, in the school environment, the idea that having a religion means being a Catholic or Evangelical Christian has no empirical support.